Plant Byproducts as Part of Edible Coatings: A Case Study with Parsley, Grape and Blueberry Pomace - Tauferova, Alexandra; Pospiech, Matej; Javurkova, Zdenka; Tremlova, Bohuslava; Dordevic, Dani; Jancikova, Simona; Tesikova, Karolina; Zdarsky, Michal; Vitez, Tomas; Vitezova, Monika (Polymers, 2021)
Studies dealing with the development of edible/biodegradable packaging have been gaining popularity since these commodities are marked as being ecofriendly, especially when byproducts are incorporated. Consequently, this study aimed at the development of chitosan-based coatings with plant byproducts. Their sensory properties, colour attributes, occurrence of cracks in microstructure and biodegradability were analysed. Coatings containing grape and blueberry pomace had statistically significantly (p < 0.05) higher levels of colour intensity. Coating samples were characterised by lower aroma intensity (3.46-4.77), relatively smooth surface (2.40-5.86), and low stickiness (2.11-3.14). In the overall hedonic evaluation, the samples containing parsley pomace in all concentrations and a sample containing 5% grape pomace achieved a statistically significantly (p < 0.05) better evaluation (5.76-5.93). The lowest values of the parameter ΔE2000 were recorded for the sample containing 5% parsley pomace (3.5); the highest was for the sample with 20% blueberry pomace (39.3). An analysis of the coating surface microstructure showed the presence of surface cracks at an 80 K magnification but the protective function of the edible coating was not disrupted by the added plant pomace. The produced samples can be considered to have a high biodegradability rate. The results of our experimentally produced coatings indicate their possible application on a commercial scale.
Keywords: CIELab; sensory; biodegradability; scanning electron microscopy; plant extracts